Attenuated Total Reflection Mid-Infrared (ATR-MIR) Spectroscopy and Chemometrics for the Identification and Classification of Commercial Tannins. Issue 11 (November 2015) - Ricci, Arianna; Parpinello, Giuseppina P.; Olejar, Kenneth J.; Kilmartin, Paul A.; Versari, Andrea
Attenuated total reflection Fourier transform infrared (FT-IR) spectroscopy was used to characterize 40 commercial tannins, including condensed and hydrolyzable chemical classes, provided as powder extracts from suppliers. Spectral data were processed to detect typical molecular vibrations of tannins bearing different chemical groups and of varying botanical origin (univariate qualitative analysis). The mid-infrared region between 4000 and 520 cm −1 was analyzed, with a particular emphasis on the vibrational modes in the fingerprint region (1800-520 cm −1 ), which provide detailed information about skeletal structures and specific substituents. The region 1800–1500 cm −1 contained signals due to hydrolyzable structures, while bands due to condensed tannins appeared at 1300–900 cm −1 and exhibited specific hydroxylation patterns useful to elucidate the structure of the flavonoid monomeric units. The spectra were investigated further using principal component analysis for discriminative purposes, to enhance the ability of infrared spectroscopy in the classification and quality control of commercial dried extracts and to enhance their industrial exploitation.